Relationship Between Personnel Management Skill And Happiness Index Among Lecturers At Higher Education Institutions In Henan Province, China - Zhang, Zhao (Journal of Mental Health and Social Rehabilitation, 2023)
The teaching profession has become one of the most stressful jobs, which has a negative impact on the performance of lecturers and their sense of well-being. The main purpose of this study is to investigate the influence of factors related to personnel management skills on the happiness index of teachers in colleges and universities. Teachers’ well-being can promote efficiency, create a positive work climate, and help achieve organizational goals and objectives. By analysing teachers’ happiness index, organizations can guarantee the sustainability of their operations. The method of this study focuses on the main quantitative methods and studies the relationship between personnel management, personnel training, personnel welfare, personnel performance evaluation, and the teacher happiness index. The survey was conducted among 300 participants to obtain sufficient data for analysis. These data were subjected to descriptive analysis, correlation analysis, and regression analysis with SPSS. It was observed that there is a strong positive correlation between personnel management and the happiness index. In order to improve the lecturer’s happiness, there is need for personnel performance appraisal. The result indicates that there is positive relation between personnel training and lecturers' happiness index. The interconnectedness among the factors influencing each other has been verified through these statistical tests. The Pearson correlation values for each of the predictors were positive with happiness index. Thus, it is evident that to improve happiness index among the lecturers, it is important to have personnel management skills.